(untitled) (Journal of Asian Development Studies, 2023)
The application of the new concept of institutionalism has gained increased prominence in the examination of comparative human resource management (HRM). This approach tends to downplay the importance of power dynamics and the interaction of contradictory logic, leading to an insufficient comprehension of the elements that influence the variance of ’HRM’ and its associated practices across different nations. The primary objective of this research is to examine Human Resource Management (HRM) practices within Pakistan’s banking industry. This study aims to assess the congruence between managers’ articulated perspectives on human resource management (HRM) practices and the prevailing ones outlined in prominent HRM models. Furthermore, the objective is to ascertain any discrepancies that may exist between the viewpoints of managers and the opinions held by early-career professionals about these human resource management methods. The influence of the cultural phenomenon referred to as ’Seth,’ characterized by a hierarchical structure reminiscent of feudalism, has implications for managers implementing human resource management (HRM) policies. This effect conflicts with the formally articulated rationale of Human Resource Management (HRM). The argument posits that managers use a "Seth" rationale when managing their workforce since it perpetuates existing power imbalances within businesses. By engaging in this activity, individuals effectively alter the nature of HRM to the extent that it becomes unrecognizable from existing models. The term ’Human Resource Management’ (HRM) in contemporary scholarly works influenced by the new institutionalism often supports a particular viewpoint on organizations and management. However, this perspective may need to be revised and might lead to misleading analysis when applied to emerging countries.